Immunoblastic morphology as a possible prognostic indicator for the outcome of the patients with diffuse large B cell lymphoma in era of the rituximab based treatment: single centre experience - Trajkova, S.; Stavridis, I. Panovska; Stojanovic, A.; Petrusevska, G.; Dukovski, D.; Ivanovski, M.; Veljanovska, A. Pivkova; Simjanovska, M. Popova; Cadievski, L.; Cevreska, L. (International Journal of Research in Medical Sciences, 2017)
Recently the results from one large prospective study indicated that immunoblastic morphology and not immunohistohemical features predict the outcome of the Diffuse large B lymphoma (DLBL). In order to investigate the prediction value of the immunoblastic morphology (IB) as a possible prognostic indicator for the outcome of our DLBL patient treated with the Rituximab (R)-CHOP regimen we conducted a retrospective study. Our study enrolled 192 DLBL patients diagnosed and treated at the University Clinic of Hematology in the period between February 2002 and December 2007. They were all treated with R-CHOP regimen and the median follow-up of the patient was 36 months. We analyzed the biopsy samples immunohistochemically for markers of germinal center (BCL6), post-germinal center (MUM1) and apoptosis (BCL2).The patients were categorized as DLBL(132; 68.7%), IB(60; 31.2). The median overall survival time (OS) were 59.3 months in DLBL group and 42.2 months in IB group, and time to treatment (TT) were 56.8 and 30.6 months respectively for the IB group. The DLBL and IB groups were comparable regarding the age, gender distributions and all others already established prognostic parameters as performance status, advanced IPI, albumin level except for the low IPI 0-2 which was statistically associated with the DLBL group (p=.024). Our results did not show any statistical survival advantage and better outcome for the patient classified as DLBL when treated with R-CHOP and indicate that immunohistohemical markers do not really reflect the molecular diversity of the tumor. Our work shows that IB morphology is a major risk factor in DLBL patients treated with R-CHOP. Therefore this morphology appears to capture some adverse molecular events that a currently hard to detect with routine diagnostic procedures.